2008
DOI: 10.1007/s00468-008-0283-y
|View full text |Cite
|
Sign up to set email alerts
|

Relationships of photosynthetic capacity to PSII efficiency and to photochemical reflectance index of Pinus taiwanensis through different seasons at high and low elevations of sub-tropical Taiwan

Abstract: We investigated the relationships of photosynthetic capacity (P (nsat), near light-saturated net photosynthetic rate measured at 1,200 mu mol m(-2) s(-1) PPFD) to photosystem II efficiency (F (v)/F (m)) and to photochemical reflectance index [PRI = (R (531) - R (570))/(R (531) + R (570))] of Pinus taiwanensis Hay. needles at high (2,600 m a.s.l) and low-elevation (800 m a.s.l) sites through different seasons. Results indicate that at high-elevation site, P (nsat), F (v)/F (m) and PRI (both measured at predawn)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 59 publications
(125 reference statements)
0
21
0
Order By: Relevance
“…To our knowledge, only one study in a Pinus taiwanensis forest pointed out that PRI is more sensitive than photosystem II efficiency to water deficits, and is closely related to photosynthetic capacity at both high-and low-elevation sites in different seasons [92]. In our study, the strongest correlation between PRI and LUE was found during the dry season (Figures 8 and 9 and Table 1), which confirms the sensitivity of PRI to water and heat stress previously reported for tropical and Mediterranean forests [87][88][89][90][91][93][94][95] and its ability to detect variations of LUE under stress conditions similar to that in other forests.…”
Section: Unresolved Questionsmentioning
confidence: 99%
“…To our knowledge, only one study in a Pinus taiwanensis forest pointed out that PRI is more sensitive than photosystem II efficiency to water deficits, and is closely related to photosynthetic capacity at both high-and low-elevation sites in different seasons [92]. In our study, the strongest correlation between PRI and LUE was found during the dry season (Figures 8 and 9 and Table 1), which confirms the sensitivity of PRI to water and heat stress previously reported for tropical and Mediterranean forests [87][88][89][90][91][93][94][95] and its ability to detect variations of LUE under stress conditions similar to that in other forests.…”
Section: Unresolved Questionsmentioning
confidence: 99%
“…Few measurements were made in the summer because of road damage by thunderstorms, typhoons and heavy rains (Weng et al 2009). Sampling procedures were the same as those used in our previous studies (Weng et al 2006b(Weng et al , 2009): current-year shoots were sampled from a southeast-facing open stand (Miscanthus) or southeastfacing branches of 2-3 m high trees growing in a mixed open stand. Shoot samples were collected before sunrise at 0600-0630 h and immediately re-cut under water.…”
Section: Measurementsmentioning
confidence: 99%
“…zeaxanthin levels (Demmig et al 1988;Adams et al 2004). The relationships between photochemical efficiency and PRI and/or between net CO 2 uptake and PRI have been examined by different irradiance levels (Peñuelas et al 1994;Gamon et al 1997;Nakaji et al 2006;Weng et al 2006aWeng et al , 2010, seasons (Nakaji et al 2006(Nakaji et al , 2007Weng et al 2006bWeng et al , 2009Weng et al , 2010 and species (Gamon et al 1997;Trotter et al 2002;Guo and Trotter 2004;Weng et al 2006a, b), at leaf to satellite scales (Garbulsky et al 2011).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations